Effect of Alkaline Metal Catalyst to Transesterification of Jatropha Curcas oil - Kurniawati, Dini (Journal of Energy, Mechanical, Material and Manufacturing Engineering, 2018)
Biodiesel is a renewable energy made of oil or fat. It is either vegetable or animal oil or fat. By using catalyst, both substances are processed by triglyceride modification to be methyl esters. This research concerned to find out the potency of alkaline (IIA) catalyst in processing biodiesel. This process initiated by testing oil free fatty acid to determine processing method. FFA value is very important in the beginning of process as it correlates to further reaction process. Temperature variation specified on 30o to 70o for 6 hours reaction. Result shows that the best methyl esters value used Mg(OH)2, Ca(OH)2 and Ba(OH)2 catalysts, respectively in 61,75%; 62,66% and 73,03%Â  on 60oC reaction temperature.